Handling Nutrition in Stunted Children Through Education and Family Education in Madura, Indonesia - Zakiyah Yasin; Ahmad Nawawi; Aulia Aprilita Sofiyana; Eka Febriyanti (Knowledge Dynamics, 2024)
Background: Stunting is a public health problem that is associated with an increased risk of morbidity, death and obstacles to both motor and mental growth.This research aims to determine the effect of family education on maternalnutritional behavior for toddlers who experience stunting in Madura, Indonesia.Method: The type of research was quantitative analytical observational, theresearch design used in this research is Quasi Experimental with a Two GroupsPre-test Post-test with Control Group Design. The population is all stuntedtoddlers who were registered at the Community Health Center in MaduraIndonesia, totaling 78 children and their mothers. The sample was 65 people usingsimple random sampling technique consisting of 33 control groups and 32treatment groups. Data collection uses a questionnaire. The variables studied arethe incidence of stunting in toddlers as the dependent variable and theindependent variable is the mother's nutritional behavior. Result: The researchresults of the Wilcoxon test analysis showed that there was a significant influenceon the average score of maternal nutritional behavior before and after being givenfamily education, with a p-value of 0.001 , namely p<0.05. Conclusion: There is aninfluence of family education on maternal nutritional behavior for toddlers whoexperience stunting in Madura Indonesia.